39. THE CLINICAL AND PARACLINICAL CHARACTERISTICS OF TWIN PREGNANCIES AT THE OBSTETRICS AND GYNECOLOGY DEPARTMENT OF THAI NGUYEN NATIONAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical characteristics of pregnant women with twins at the Obstetrics and Gynecology Center of Thai Nguyen Central Hospital from June 2021 to June 2023.Research subjects and methods: Cross-sectional descriptive study with retrospective sampling based on medical record information of 105 pregnant women with twins ≥ 22 weeks gestational age at Thai Nguyen Central Hospital from June 1, 2021 to June 30, 2023.Results: The average age of pregnant women was 29.34 ± 5.12 years old and the age group 21-34 accounted for the highest proportion (81.0%). 61.9% of pregnant women ended their pregnancy after 37 weeks. The number of pregnant women giving birth to multiples accounts for 47.6%. Among pregnant women who used assisted reproductive methods, the majority was IVF (48.6%). Prenatal ultrasound had the highest rate of dichorionic twins (59.1%). The rate of polyhydramnios is 1.9%, oligohydramnios is 3.8%. The rate of pregnant women with anemia before giving birth is 20.0%. There are 9.5% of pregnant women with gestational diabetes.Conclusion: Pregnant women are mainly of reproductive age. Among pregnant women who used assisted reproductive methods, the majority were IVF (48.6%). Mostly twin pregnancies with 2 placenta and 2 amniotic chambers (59.1%). The rate of pregnant women with antepartum anemia and gestational diabetes is low and the majority give birth after 37 weeks.
Keywords: Twin pregnancy; IVF; dichorionic-two amniotic twins